High-quality development under energy constraints: an empirical study based on e-commerce demonstration zones - Guo, Qian; Zhang, Na (Frontiers in Energy Research, 2024)
Introduction: China is exploring methods to achieve economically intensive, green, and high-quality development. Strengthening urban green total-factor production is important for achieving high-quality economic development. Whether the construction of e-commerce demonstration zones (EDZ) can provide new opportunities for high-quality urban development under the dual constraints of energy and environment is a question worth studying. Methods: In order to verify the relationship this study using panel data from 290 prefecture-level cities in China from 2005 to 2020. Data envelopment analysis (DEA) was used to assess the level of high-quality urban development under resource and environmental constraints. The multi-phase difference-difference method (DID) was used to analyze how the e-commerce model city creation policies significantly promoted high-quality urban economic development. Results and Discussion: This study shows that the e-commerce demonstration zone effectively promotes the high-quality development of the city. Heterogeneity tests show that the impact of electric EDZs on high-quality development can be influenced by city size and geographic location (e.g., east coast and mid-west). Based on these conclusions, this study puts forward some suggestions to enhance the attractiveness of small- and medium-sized cities, non-resource-based cities, and western cities by formulating preferential policies.